Dampak Terpaan Berita Kekerasan di Media terhadap Tingkat Kecemasan Mahasiswa di Yogyakarta - Fangi Latun Faorin; Aisyah Aisyah (CV. Lentera Literasi Indonesia, 2026)
The level of anxiety in college students is influenced by various psychological and environmental factors, one of which is exposure to violent news widely disseminated through mass media and digital media. Continuous consumption of violent news can shape the view that the world is unsafe, thus potentially triggering increased anxiety in students who actively access media. This study aims to determine the impact of exposure to violent news in the media on the anxiety levels of college students in Yogyakarta. The method used in this study is quantitative descriptive with data collection techniques through an online questionnaire using a Likert scale. The research subjects were 100 active college students domiciled in the Special Region of Yogyakarta. The data analysis process was carried out through validity tests, reliability tests, normality tests, linearity tests, and simple linear regression analysis. The results showed that all research instruments were declared valid and reliable, and the data were normally distributed and had a linear relationship. A simple linear regression test showed a significant effect between exposure to violent news in the media on students' anxiety levels with a significance value of p < 0.05. The coefficient of determination (R Square) of 0.386 indicates that exposure to violent news contributed 38.6% to students' anxiety levels, while 61.4% was influenced by other factors outside this study.